Pengaruh Customer Feedback Terhadap Peningkatan Service Quality Dimediasi Loyalitas Konsumen Pada PT. Pos Indonesia - Masruroh (CV. Multi Kreasi Media, 2024)
This research examines the influence of customer feedback on improving service quality, as well as the role of consumer loyalty as a mediator in this relationship. This research uses quantitative sampling techniques with purposive sampling with the criteria that respondents have previously provided feedback to PT. Pos Indonesia sub-district branch. Paciran, sample size 100 respondents. are customers. The analysis method uses Smart PLS. The results of testing the first hypothesis (H1) show that customer feedback has a positive influence on the service quality variable. This shows that feedback that is received and responded to well by the organization can increase service excellence. The results of testing the second hypothesis show that consumer loyalty can be a mediator in the relationship between customer feedback and service excellence.